The socio-ecological complexity of facing climate change: a case study from Pima County (Arizona, USA) - Le Tourneau, François-Michel; Fisher, Larry A.; Zuniga-Teran, Adriana A.; Wilder, Benjamin T.; Boyer, Anne-Lise; Blanchon, David; Dubertret, Fabrice (Comptes Rendus. Géoscience)
Socio-ecological systems are in constant transformation and adaptation, with dynamic and constant interaction between the social and environmental dimensions. This reality requires interdisciplinary studies, or a holistic approach sometimes referred to as “global ecology”, to address that complexity at every level in their analysis. “Human-environment observatories” (Observatoires Hommes-Milieux, OHM) are an ideal setting to develop such studies since they are inherently interdisciplinary and develop both short and long-term perspectives on specific socio-ecological systems. Pima County observatory (OHMi-PC), located in Arizona (USA), is one of the 13 “Human-Environment observatories” of the DRIIHM LabEx. In this paper, we show how we can apply the DRIIHM framework to Pima County and how this allows for innovative interdisciplinary approaches of issues related to environmental and human dynamics in southeastern Arizona, such as the dynamics of wildfires, which we show to be related to human as well as environmental factors, the restauration of the Santa Cruz river, which we analyze as ambiguous in terms of ecology, or the Cienega creek area, where the OHMi-PC has been involved in local landscape conservation efforts.